PRAKTIK PENGASUHAN ORANG TUA PEKERJA SEKS KOMERSIAL DAN IMPLIKASINYA TERHADAP PENDIDIKAN ANAK (Studi kasus di Desa Permata Baru, Kecamatan Indralaya Utara) - Syawalludin; Shomedran; Ardi Saputra; Henny Helmi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze parenting patterns in shaping children's education within families of commercial sex workers (CSWs) in Permata Baru Village, North Indralaya District, Ogan Ilir Regency. This research uses a qualitative descriptive approach with data collected through observation, interviews, and documentation. The results show that the dominant parenting style is authoritarian, influenced by limited time, economicconditions, and the social environment. Parents’ low educational background and social stigma also affect children's educational development. The study concludes that children's education in CSW families is influenced by both family and social environmental factors, requiring support from various parties to create a conducive educational environment.